2019
DOI: 10.1007/s10551-019-04269-7
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Character-Based Judgement in the Professional Domain

Abstract: Dimensions of character are often overlooked in professional practice at the expense of the development of technical competence and operational efficiency. Drawing on philosophical accounts of virtue ethics and positive psychology, the present work attempts to elevate the role of 'good' character in the professional domain. A 'good' professional is ideally one that exemplifies dimensions of character informed by sound judgement. A total of 2340 professionals, from five discrete professions, were profiled based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 86 publications
2
10
0
2
Order By: Relevance
“…For example, an excess of determination and confidence in students may be interpreted as arrogance or insensitivity in the absence of empathy and compassion. This operationalization of character is consistent with the idea that every virtue may become a vice if not correctly applied in a specific situation (e.g., Arthur et al, 2019;Crossan et al, 2017;Gillham et al, 2011).…”
Section: Charactersupporting
confidence: 83%
See 2 more Smart Citations
“…For example, an excess of determination and confidence in students may be interpreted as arrogance or insensitivity in the absence of empathy and compassion. This operationalization of character is consistent with the idea that every virtue may become a vice if not correctly applied in a specific situation (e.g., Arthur et al, 2019;Crossan et al, 2017;Gillham et al, 2011).…”
Section: Charactersupporting
confidence: 83%
“…Many character scholars anchor their discussion of character in virtuous character (e.g., Arthur et al, 2019;Crossan et al, 2017;Hannah & Avolio, 2011;Newstead et al, 2019). Foundational to this stream of research is the cross-national and cross-cultural work of Christopher Peterson and Martin Seligman.…”
Section: Charactermentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they revealed that moral motivational aspects of character-the desire of being a moral person and empathicconcern emotions-appear to be connected to career-related engagement and the absence of career indecision. This key contribution is in line with the latest research bridging social science with moral philosophy in the domain of professional development [99][100][101]. Our findings corroborate the importance of moral motivation for academic and career success.…”
Section: Discussionsupporting
confidence: 88%
“…Further evidence of the role of moral virtues was observed in topics such as the relationships between buyer-seller (Donada, Mothe, Nogatchewsky, & Ribeiro, 2019); leader-led (Qin et al, 2019); managers-salespeople (Shanahan & Hopkins, 2019); the professionals' character (Arthur et al, 2021); and responsible consumption (Song & Kim, 2018).…”
Section: Development and Application Of Scales On Moral Virtuesmentioning
confidence: 99%